Impact of Spatial Noise Correlation on Bearing Accuracy in DIFAR Systems - RUDNICKI, Mariusz; MARSZAL, Jacek; SALAMON, Roman (Archives of Acoustics, 2020)
DIFAR type underwater passive systems are one of the more commonly used tools for detecting submarines. At the design stage, which usually uses computer simulations, it is necessary to generate acoustic noise of the sea. It has been shown that correlating noise significantly reduces these errors compared to the assumption that noise is uncorrelated. In addition, bearing errors have been shown to be the same in systems with a commonly used antenna containing five hydrophones, as in a system without a central hydrophone, which may be useful in some DIFAR system design solutions.